OECS Private Sector Financing : Ridging the Supply-Demand Gap - World Bank (Washington, DC, 2013)
The high levels of public debt and persistent fiscal deficits limit Organization of Eastern Caribbean States (OECS) governments' ability to pursue counter-cyclical fiscal policies during future economic downturns, leaving private investment as the key driver of future growth. This study on private sector financing in the OECS analyzes the issue of access to finance from three different angles: the demand side; the supply side; and the enabling environment. It is not possible to fully analyze problems of access to finance without a broad approach. Demand side, supply side and the enabling environment are jointly analyzed in this study to identify key measures that could be applied in order to improve the enabling environment, create better opportunities for business growth and innovation (diversification), and place financial sector institutions in a position to provide finance, especially to SMEs, in a sustainable way.